FIJI: A Framework for the Immersion-Journalism Intersection - Hardee, Gary M.; McMahan, Ryan P. (Frontiers in ICT, 2017)
As journalists experiment with developing immersive journalism—first-person, interactive experiences of news events—guidelines are needed to help bridge a disconnect between the requirements of journalism and the capabilities of emerging technologies. Many journalists need to better understand the fundamental concepts of immersion and the capabilities and limitations of common immersive technologies. Similarly, developers of immersive journalism works need to know the fundamentals that define journalistic professionalism and excellence and the key requirements of various types of journalistic stories. To address these gaps, we have developed a Framework for the Immersion-Journalism Intersection (FIJI). In FIJI, we have identified four domains of knowledge that intersect to define the key requirements of immersive journalism: the fundamentals of immersion, common immersive technologies, the fundamentals of journalism, and the major types of journalistic stories. Based on these key requirements, we have formally defined four types of immersive journalism that are appropriate for public dissemination. In this article, we discuss the history of immersive journalism, present the four domains and key intersection of FIJI, and provide a number of guidelines for journalists new to creating immersive experiences.